Pengaruh ketiadaan inang terhadap tanggap reproduksi Trichogrammatoidea armigera Nagaraja dan Trichogramma japonicum Ashmed (Hymenoptera: Trichogrammatoidea) dan implikasinya terhadap penerimaan inang - Anis Rohmani; Damayanti Buchori; Adha Sari (Jurnal Entomologi Indonesia, 2008)
Trichogrammatoidea armigera and Trichogramma japonicum are polyphagous egg parastioids, that are important as natural enemies. The objective of this research was to study the effect of host deprivation on reproductive capacity of T. armigera and T. japonicum. This study consists of 8 treatments, host deprivation : 0 hour, 1 hour, 2 hours, 3 hours, 6 hours, 12 hours, and 48 hours. Host were replaced every 24 hours. Results showed there are difference with respect of how the two parasitoids respond to the treatment. Deprivation of host for 3 hours in T. armigera resulted in the increase of egg production and parasitism rate. After 12 and 24 hours of not encountering any hosts, the numbers of eggs produced drastically decreased. Treatment on T. japonicum resulted in the reaction of fecundity and parasitism rate overall. Forty eight hours of host deprivation resulted in death of both parasitoids species within 2 days. None of the parasitoids seems to produce any egg.